The microwave processing of foods - Regier, Marc; Knoerzer, Kai; Schubert, Helmar (Woodhead Publishing Series in Food Science, Technology and Nutrition, 2017)
The Microwave Processing of Foods, Second Edition, has been updated and extended to include the many developments that have taken place over the past 10 years. Including new chapters on microwave assisted frying, microwave assisted microbial inactivation, microwave assisted disinfestation, this book continues to provide the basic principles for microwave technology, while also presenting current and emerging research trends for future use development. Led by an international team of experts, this book will serve as a practical guide for those interested in applying microwave technology. Provides thoroughly up-to-date information on the basics of microwaves and microwave heatingDiscusses the main factors for the successful application of microwaves and the main problems that may ariseIncludes current and potential future applications for real-world application as well as new research and advancesIncludes new chapters on microwave-assisted frying, microbial inactivation, and disinfestation.